The Increase of Insect Pest Population in Paddy Field Managed with an Ecological Approach using Refugia Plants and Biopesticides - Alprilia, Arieska Wahyu; Windiyanti, Wiwin; Kusuma, Ramadhani Mahendra (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2024)
Insect pests can damage plants and act as vectors of diseases such as brown planthoppers which can transmit dwarf virus disease. The presence of insect pests is influenced by the type of variety, planting patterns, and excessive use of chemical pesticides so that insect pests increase and are difficult to control. This research wanted to provide insights into the effectiveness of combining insectary plants and biopesticides as ecological strategies to manage paddy (Oryza sativa Linnaeus) insect pests. The study was conducted in February-April 2024 in Sukodadi Village, Sukodadi District, Lamongan Regency. Method of study was conducted using a combination of direct observation, insect traps, and quantitative analysis to evaluate the impact of refugia plants and biopesticides on insect pest populations in paddy fields. The analysis includes the species diversity index (Shannon-Winner), species evenness index, species richness index (Margalef), dominance index (Simpson) and similarity index (Bray-Curtis). The study obtained 2,687 individual insect pests in paddy fields with refugia and fobio and 1,761 individuals in paddy fields without refugia and fobio. Insect pests were more abundant in paddy fields with refugia and fobio compared to fields without refugia and fobio. Refugia provides alternative habitats and additional resources for insect pests, and the use of biopesticides can create temporary ecosystem imbalances, and increase the population of insect pest.